Development of 3D Cell-Based Fluorescent Reporter Assay for Screening of Drugs Downregulating Telomerase Reverse Transcriptase - You Li; Fengli Zhang; Zhen Qin; Shang-Tian Yang (Bioengineering)
A fluorescent cell-based assay was developed for the screening of chemicals repressing the expression of human telomerase reverse transcriptase (hTERT). hTERT is reactivated during carcinogenesis and is overexpressed in more than 90% of cancers but is almost silent in normal tissue cells. Because of its critical role in cancer, hTERT is a target in various therapeutic strategies for cancer treatment. In this study, the hTERT promoter was cloned in MCF7 breast cancer cells and used to control the expression of enhanced green fluorescent protein (EGFP). The fluorescence of EGFP indicated the activity of the hTERT promoter, and, in the presence of an hTERT repressor, the EGFP fluorescence signal was reduced as compared to the EGFP fluorescence controlled by the human cytomegalovirus (CMV) promoter, which was not affected by changes in culture conditions and worked as a control. The EGFP reporter cells were cultivated in three-dimensional (3D) microbioreactors to resemble the in vivo tumor physiology and provide in vivo-like responses. The assay’s predictability was demonstrated with three known hTERT inhibitors, pristimerin, epigallocatechin gallate, and n-butylidenephthalide, and further evaluated with five widely used anticancer compounds, doxorubicin, cisplatin, paclitaxel, blasticidin, and tamoxifen. The results showed overall accuracy of over 83.3%, demonstrating the feasibility of using the hTERT promoter with EGFP as a reporter for the screening of potential cancer drugs targeting hTERT.